DNA Fingerprint Databases of Chengal (Neobalanocarpus Heimii) For Forensic Forestry Investigations - Tnah, Lee Hong (2007)
Illegal logging poses a significant threat to the sustainability of Malaysian forest ecosystems. Presently, foresters have to depend on wood anatomical evidences to link the suspected timber thefts to the source trees but this is inconclusive. This study was aimed to utilize DNA markers in plant DNA fingerprinting for forensic applications using Neobalanocarpus heimii as a model. To generate a comprehensive DNA database of N. heimii for individual identification, 30 natural populations were identified from 27 forest reserves, and a total of 1081 individuals were collected throughout Peninsular Malaysia. An extensive evaluation of 51 short tandem repeat (STR) loci developed for Dipterocarpaceae managed to identify 12 STR loci, which showed specific amplification, absence of null alleles, single-locus mode of inheritance, and absence of mononucleotide repeat motifs in N. heimii. Cluster analyses via assignment test and genetic distance divided the 30 populations into three genetic clusters, corresponding to three geographical regions: Region A (west), Region B (central and south) and Region C (northeast). DNA databases of N. heimii were constructed and characterized at the levels of population, region and Peninsular Malaysia. Independence tests showed that the majority of the loci significantly deviated from Hardy-Weinberg equilibrium due to population substructuring and inbreeding. Thus, the match probability of N. heimii should be estimated using the ‘subpopulation-cum-inbreeding model’ that adjusted for coancestry (θ) and inbreeding (f) coefficients. The conservativeness tests showed that both the regional and Peninsular Malaysian databases were conservative and should be adequate to predict allele and genotype frequencies of N. heimii throughout Peninsular Malaysia. With a combined power of discrimination of more than 0.99999999999999999, the Peninsular Malaysian database should be able to provide legal evidences for court proceedings against illegal loggers on N. heimii. The comprehensive DNA fingerprinting databases developed for N. heimii are the first reported for a tropical tree species and the methodology developed should be able to serve as a model for the study of other important timber species in Malaysia. The availability of DNA fingerprinting databases for the majority of important timber species in Malaysia would enhance the capacity of Forest Department officials to curb the problem of illegal logging and this would indirectly ensure the conservation and sustainable utilization of forest resources in Malaysia.